Vibration damper
Patent Information
- Application Number
- JP2024192076
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-17
- Estimated Expiration
- 2044-10-31
AI Technical Summary
【0010】 本発明によれば、制振ダンパーにおける減衰特性の低下を抑制できる。
Smart Images

Figure 0007630703000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a vibration damper, and more particularly to a vibration damper suitable for applications such as vibration control and seismic isolation in the fields of civil engineering and construction. [Background technology]
[0002] In the fields of civil engineering and construction, vibration control devices and seismic isolation devices, particularly vibration dampers (also called seismic isolation dampers) used in large structures such as bridges and buildings, it is required that the mechanical structural elements of the vibration control damper exert vibration control performance in order to absorb vibration energy caused by earthquakes, etc., and that the viscoelastic material (rubber material) used in the vibration control damper achieve high damping.
[0003] Furthermore, the 2016 Ministry of Land, Infrastructure, Transport and Tourism guidelines included instructions on how to respond to long-period earthquake motion (convergence time of 600 seconds) for high-rise buildings, and this has created a growing need for vibration control dampers whose damping characteristics do not decrease even with shaking that has a long convergence time.
[0004] Viscoelastic bodies used in conventional vibration dampers mainly contain a styrene-isoprene-styrene (SIS) copolymer as a main component (see, for example, Patent Documents 1 and 2). In addition, in order to develop friction damping properties for SIS copolymers, investigations are being conducted into blending them with ethylene-propylene-diene terpolymers or with small particle size fillers such as silica or calcium carbonate. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2014-227521 A [Patent Document 2] JP 2015-183110 A Summary of the Invention [Problem to be solved by the invention]
[0006] In the manufacture of vibration dampers, adhesives are used to bond the viscoelastic body and metal that constitute the vibration damper. However, depending on the storage period and storage environment of the vibration damper after manufacture, the crosslinking agent and crosslinking accelerator (hereinafter, these may be collectively referred to as "crosslinking agent") contained in the adhesive may migrate or diffuse into the uncrosslinked viscoelastic body, increasing the crosslink density in the vicinity of the adhesive interface of the viscoelastic body, which may reduce the damping characteristics of the vibration damper.
[0007] The present invention has been made in consideration of the above circumstances, and has an object to provide a vibration damper that can suppress a decrease in damping characteristics. [Means for solving the problem]
[0008] The present inventors conducted extensive research with a view to suppressing the deterioration of the damping characteristics of a vibration damper due to migration of a crosslinking agent, and unexpectedly discovered that the deterioration of damping characteristics can be suppressed by using an uncrosslinked viscoelastic body made of a rubber composition containing (A) at least one of a styrene-isoprene-styrene (SIS) copolymer and a styrene-butadiene-styrene (SBS) copolymer, and (B) one or more selected from the group consisting of ethylene-propylene-diene terpolymer (EPDM), ethylene-butene-diene terpolymer (EBT), and butadiene rubber (BR), and an adhesive made of an adhesive containing a crosslinking agent, and by controlling the thickness of the cured portion formed by the crosslinking agent that has migrated from the adhesive layer into the uncrosslinked viscoelastic body layer within a specific range.
[0009] That is, the gist of the present invention is the following [1] to [5]. [1] A metal layer; An adhesive layer made of an adhesive containing a crosslinking agent; A vibration damper including a layer structure formed by laminating, in this order, an uncrosslinked viscoelastic layer made of a rubber composition containing the following components (A) and (B): A vibration damper having a hardened portion having an elastic modulus of more than 1.2 MPa formed by the crosslinking agent that has migrated from the adhesive layer into the uncrosslinked viscoelastic layer, and the thickness of the hardened portion is in the range of 75 μm or less. (A) At least one of a styrene-isoprene-styrene copolymer and a styrene-butadiene-styrene copolymer (B) one or more selected from the group consisting of ethylene-propylene-diene terpolymer, ethylene-butene-diene terpolymer, and butadiene rubber [2] The vibration damper according to [1], wherein the thickness of the hardened portion is in the range of 50 μm or less. [3] The vibration damper according to [1] or [2], wherein the rubber composition further contains at least one of calcium carbonate and silica. [4] The vibration damper according to any one of [1] to [3], wherein the crosslinking agent is an aromatic nitroso compound, and the content of the aromatic nitroso compound is 0.1 to 50 mass % based on the total solid content in the adhesive. [5] The vibration damper according to any one of [1] to [4], wherein the uncrosslinked viscoelastic layer has a thickness of 3 to 40 mm, and the adhesive layer has a thickness of 5 to 40 μm. Effect of the Invention
[0010] According to the present invention, it is possible to suppress the deterioration of the damping characteristics of the vibration damper.
[0011] According to one embodiment of the present invention, the increase in crosslink density of the uncrosslinked viscoelastic body caused by the crosslinking agent contained in the adhesive, i.e., the formation of hardened parts, can be suppressed, thereby suppressing the deterioration of the damping characteristics of the vibration damper.
[0012] More specifically, according to one embodiment of the present invention, the thickness of the hardened portion formed due to the migration of the crosslinking agent contained in the adhesive to the uncrosslinked viscoelastic layer depending on the storage period and storage environment of the vibration damper after manufacture is controlled to a range of 75 μm or less, which effectively prevents a decrease in the damping characteristics of the vibration damper and, more preferably, is extremely useful in maintaining good interlayer adhesion characteristics between the metal layer and the uncrosslinked viscoelastic layer. [Brief description of the drawings]
[0013] [Figure 1] FIG. 2 is a front view showing an example of a vibration damper. [Diagram 2] FIG. 2 is a cross-sectional view showing an example of a vibration damper. [Diagram 3] FIG. 11 is a cross-sectional view showing another example of the vibration damper. [Figure 4] FIG. 2 is a schematic diagram showing an installation state of a vibration damper. [Diagram 5] FIG. 1 is a schematic diagram of an apparatus used to carry out the evaluation methods described in the Examples. [Figure 6] FIG. 2 is a diagram showing a load-strain loop curve in the evaluation method described in the Examples. [Figure 7] FIG. 2 is a schematic partial cross-sectional view for explaining the layer structure of the vibration damper. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Next, an embodiment of the present invention will be described in detail, although the present invention is not limited to this embodiment.
[0015] In this specification, "X or / and Y (X and Y are optional)" means at least one of X and Y, and means the following three cases: X only, Y only, and X and Y. In addition, for the numerical ranges described in stages in this specification, the upper limit or lower limit of a certain numerical range can be arbitrarily combined with the upper limit or lower limit of another numerical range. In addition, in the numerical ranges described in this specification, the upper limit or lower limit of the numerical range can be replaced with the value shown in the examples.
[0016] A vibration damper according to one embodiment of the present invention (hereinafter sometimes referred to as "this vibration damper") has a layered structure formed by laminating, in this order, a metal layer, an adhesive layer (hereinafter sometimes referred to as "this adhesive layer") consisting of an adhesive containing a crosslinking agent, and an uncrosslinked viscoelastic layer (hereinafter sometimes referred to as "this viscoelastic layer" or simply "viscoelastic layer") consisting of a rubber composition (hereinafter sometimes referred to as "this rubber composition") containing the following components (A) and (B), and is characterized in that it has a cured portion with an elastic modulus of greater than 1.2 MPa formed by the crosslinking agent that has migrated from the adhesive layer into the viscoelastic layer, and the thickness of the cured portion is in the range of 75 μm or less. (A) At least one of a styrene-isoprene-styrene copolymer and a styrene-butadiene-styrene copolymer (B) one or more selected from the group consisting of ethylene-propylene-diene terpolymer, ethylene-butene-diene terpolymer, and butadiene rubber
[0017] As mentioned above, when the crosslinking agent of the adhesive layer migrates into the viscoelastic layer, the crosslinking density in the vicinity of the adhesive interface of the viscoelastic layer increases, forming a hardened portion, which may reduce the damping characteristics of the vibration damper. According to one embodiment of the vibration damper, the thickness of the hardened portion formed by the crosslinking agent migrated into the viscoelastic layer is controlled to a specific range of 75 μm or less, so that the damping characteristics are excellent. If the thickness of the hardened portion is outside the above range, the excellent damping characteristics of the present invention cannot be obtained. For example, if the thickness of the hardened portion exceeds 75 μm, the excellent damping characteristics of the present invention cannot be obtained.
[0018] Furthermore, according to a preferred embodiment of the vibration damper, the thickness of the hardened portion formed by the crosslinking agent that has migrated from the adhesive layer into the viscoelastic layer is controlled to a specific range of 75 μm or less, resulting in excellent interlayer adhesion properties, and is extremely useful in that it provides excellent both damping properties and interlayer adhesion properties.
[0019] Although the reason why this vibration damper achieves the above-mentioned excellent effects is not entirely clear, the inventors surmise that by restricting the thickness of the hardened portion (sometimes referred to as the "crosslinking agent migration layer") formed by the migration of the crosslinking agent in the adhesive layer to a specific thinness, it is possible to exhibit an excellent spring effect while maintaining the interlayer adhesion properties, and it is also possible to functionally separate each layer in the layered structure consisting of the hardened portion, viscoelastic layer, and metal layer, so that each layer operates efficiently to exhibit excellent damping properties.
[0020] The hardened portion is formed due to the crosslinking agent contained in the adhesive migrating into the viscoelastic layer, resulting in an increase in the crosslinking density of the viscoelastic body in the vicinity of the adhesive layer interface, and has a higher elastic modulus than the viscoelastic body. In the present invention, the hardened portion means a portion between the adhesive layer interface and the viscoelastic body layer that has an elastic modulus of more than 1.2 MPa, and the thickness of the hardened portion is defined as the thickness of the hardened portion. The upper limit of the elastic modulus is not particularly limited, but is usually 2.5 MPa or less.
[0021] The thickness of the hardened portion can be determined in a conventional manner by the following method. The metal layer, the adhesive layer, and the viscoelastic layer constituting the vibration damper are cut to prepare a smooth cross section, and the elastic modulus is measured using a microhardness tester. The thickness of the thickness direction region in the range from the adhesive layer interface to the viscoelastic layer where the elastic modulus is more than 1.2 MPa is defined as the thickness of the cured portion. The elastic modulus is measured using a microhardness tester under the following measurement conditions, for example. [Elastic modulus measurement conditions] Microhardness tester: Fischer Instruments FISCHERSCOPE HM2000 Vickers diamond indenter: square pyramid Load: 0~200mN Press time: 2 seconds Maximum load retention (creep) time: 5 seconds Load release time: 2 seconds
[0022] In one embodiment of the present vibration damper, the layer structure is made up of "metal layer / present adhesive layer / present viscoelastic layer / present adhesive layer / metal layer," and hardened portions (two hardened portions) are formed near each interface of the two present adhesive layers. It is sufficient that the thickness of at least one of the hardened portions is controlled to a specific range of 75 μm or less, and it is more preferable that the thicknesses of both hardened portions are each controlled to a specific range of 75 μm or less.
[0023] Each layer constituting the vibration damper will now be described in detail.
[0024] [Viscoelastic layer] The viscoelastic layer constituting the vibration damper is formed from a viscoelastic body made of the rubber composition containing components (A) and (B).
[0025] In one embodiment of the vibration damper, the rubber composition contains at least the polymer components (A) and (B). The polymer components are preferably a polymer component containing the polymer component (A) as a main component.
[0026] The "main component" of the above polymer component means that component (A) accounts for 50 mass% or more of the total amount (100 mass%) of the above polymer component, and may be 60 mass% or more, 70 mass% or more, 80 mass% or more, or 90 mass% or more.
[0027] Furthermore, in one embodiment of the present vibration damper, from the viewpoint of damping characteristics, it is preferable that the polymer component consists only of component (A) and component (B). However, this is not limited to this. For example, of the total amount (100 mass%) of the polymer component, the content of components (A) and (B) may be 60 mass% or more, 70 mass% or more, 80 mass% or more, 90 mass% or more, 95 mass% or more, etc.
[0028] (A) At least one of styrene-isoprene-styrene (SIS) copolymer and styrene-butadiene-styrene (SBS) copolymer The rubber composition contains at least one of a styrene-isoprene-styrene (SIS) copolymer and a styrene-butadiene-styrene (SBS) copolymer. The styrene-isoprene-styrene (SIS) copolymer and the styrene-butadiene-styrene (SBS) copolymer are styrene-based elastomers, and those conventionally known in the art can be used as appropriate.
[0029] (Styrene-isoprene-styrene (SIS) copolymer) The styrene-isoprene diblock content in the SIS copolymer is not particularly limited, but is preferably 50 to 95% by mass, and more preferably 60 to 90% by mass. With such a diblock content, it is more excellent in obtaining high damping characteristics. The diblock content is a value measured by gel permeation chromatography (GPC).
[0030] The styrene content in the SIS copolymer is not particularly limited, but is preferably 10 to 30 mass %, and more preferably 13 to 25 mass %. The styrene content is a value measured by a nuclear magnetic resonance (NMR) spectrometer.
[0031] The number average molecular weight (Mn) of the SIS copolymer is not particularly limited, but is preferably 100,000 to 200,000, and more preferably 100,000 to 150,000. In other words, such a small molecular weight is preferable from the viewpoint of damping characteristics. The number average molecular weight (Mn) is a value measured according to gel permeation chromatography (GPC).
[0032] Mooney viscosity (ML) of SIS copolymer 1+4 (100° C.) is not particularly limited, but is preferably from 10 to 50, and more preferably from 13 to 40, for example.
[0033] The Mooney viscosity in this specification is measured in accordance with the provisions of JIS K6300-1:2013 using an L-shaped rotor under conditions of a preheating time of 1 minute, a rotor rotation time of 4 minutes, and a test temperature of 100°C.
[0034] (Styrene-butadiene-styrene (SBS) copolymer) The styrene-butadiene diblock content in the SBS copolymer is not particularly limited, but is preferably 50 to 95% by mass, and more preferably 60 to 90% by mass. With such a diblock content, it is more excellent in obtaining high damping characteristics. The diblock content is a value measured by gel permeation chromatography (GPC).
[0035] The styrene content in the SBS copolymer is not particularly limited, but is preferably 10 to 30% by mass, and more preferably 13 to 25% by mass, for example. The styrene content is a value measured by a nuclear magnetic resonance (NMR) spectrometer.
[0036] The number average molecular weight (Mn) of the SBS copolymer is not particularly limited, but is preferably in the range of 100,000 to 200,000, and more preferably in the range of 100,000 to 150,000. In other words, such a small molecular weight is preferable from the viewpoint of damping characteristics. The number average molecular weight (Mn) is a value measured according to gel permeation chromatography (GPC).
[0037] Mooney Viscosity (ML 1+4 (100° C.) is not particularly limited, but is preferably from 10 to 50, and more preferably from 13 to 40, for example.
[0038] The rubber composition may contain other components as polymer components than those mentioned above. For example, styrene-based elastomers such as styrene-butadiene (SB) copolymer, styrene-isoprene (SI) copolymer, styrene-ethylene-butylene (SEB) copolymer, styrene-ethylene-butylene-styrene (SEBS) copolymer, styrene-ethylene-propylene (SEP) copolymer, styrene-ethylene-propylene-styrene (SEPS) copolymer, and hydrogenated copolymers of the above-mentioned copolymers may be mentioned. These may be used alone or in combination of two or more kinds.
[0039] Examples of commercially available products of the component (A) include Quintac 3390, Quintac 3433N, and Quintac 3270 (all manufactured by Zeon Corporation), D1161 (manufactured by Kraton Polymers), and VECTOR 4411 (manufactured by TSRC Corporation).
[0040] (B) One or more selected from the group consisting of ethylene-propylene-diene terpolymer, ethylene-butene-diene terpolymer, and butadiene rubber The rubber composition contains at least one rubber selected from the group consisting of an ethylene-propylene-diene terpolymer, an ethylene-butene-diene terpolymer, and a butadiene rubber.
[0041] (Ethylene-propylene-diene monomer terpolymer (EPDM)) Any EPDM known in the art can be used as appropriate. The ethylene content of the EPDM is not particularly limited, but is preferably 5 to 60 mass %, more preferably 10 to 40 mass %, from the viewpoint of damping characteristics.
[0042] The propylene content of EPDM is not particularly limited, but is preferably from 5 to 60 mass %, more preferably from 10 to 40 mass %, from the viewpoint of damping characteristics, for example.
[0043] The diene content of the EPDM is not particularly limited, but from the viewpoint of damping characteristics, it is preferably from 3 to 25 mass %, and more preferably from 5 to 15 mass %.
[0044] The diene (third component) of EPDM is preferably a diene monomer having 5 to 20 carbon atoms, and specific examples thereof include 1,4-pentadiene, 1,4-hexadiene, 1,5-hexadiene, 2,5-dimethyl-1,5-hexadiene, 1,4-octadiene, 1,4-cyclohexadiene, cyclooctadiene, dicyclopentadiene (DCP), 5-ethylidene-2-norbornene (ENB), 5-butylidene-2-norbornene, 2-methallyl-5-norbornene, and 2-isopropenyl-5-norbornene.
[0045] EPDM Mooney Viscosity (ML 1+4 (100° C.) is not particularly limited, but is preferably in the range of, for example, 30 to 100, and more preferably 35 to 85.
[0046] (Ethylene-butene-diene terpolymer (EBT)) As the EBT, any EBT conventionally known in the art can be used as appropriate. The ethylene content of the EBT is not particularly limited, but is preferably, for example, 55 mass% or less, more preferably 35 to 55 mass%, and further preferably 40 to 53 mass%.
[0047] The butene content in EBT is not particularly limited, but is, for example, preferably 35% by mass or more, more preferably 35 to 55% by mass, and further preferably 38 to 50% by mass.
[0048] The diene content of EBT is not particularly limited, but from the viewpoint of damping characteristics, it is preferably 3 to 25 mass %, and more preferably 5 to 15 mass %.
[0049] The diene (third component) of EBT is preferably a diene monomer having 5 to 20 carbon atoms, and specific examples thereof include 1,4-pentadiene, 1,4-hexadiene, 1,5-hexadiene, 2,5-dimethyl-1,5-hexadiene, 1,4-octadiene, 1,4-cyclohexadiene, cyclooctadiene, dicyclopentadiene (DCP), 5-ethylidene-2-norbornene (ENB), 5-butylidene-2-norbornene, 2-methallyl-5-norbornene, and 2-isopropenyl-5-norbornene.
[0050] (Butadiene rubber (BR)) The butadiene rubber (BR) used in the rubber composition can be any rubber that is conventionally known in the art. The butadiene rubber (BR) is a rubber obtained by polymerizing butadiene as a raw material monomer, and is obtained by polymerizing butadiene using, for example, a Ziegler catalyst or an alkyl lithium initiator.
[0051] The microstructure of the butadiene rubber (BR) is not particularly limited, but a low cis-BR having a cis-1,4 bond unit content of 50% by mass or less, for example, about 30 to 40% by mass, or a high cis-BR having a cis-1,4 bond unit content of 90% by mass or more can be appropriately used.
[0052] Butadiene rubber (BR) Mooney viscosity (ML 1+4 (100° C.) is not particularly limited, but is, for example, about 30 to 60, 30 to 55, or 30 to 50.
[0053] Commercially available products of the component (B) include, for example, EPT 4045M (all manufactured by Mitsui Chemicals), EP104E, EP35, EP65, EP33, and EP98 (all manufactured by JSR Corporation).
[0054] The mixing ratio of the components (A) and (B) in the rubber composition is preferably (A):(B)=95:5 to 50:50 by mass, and more preferably (A):(B)=90:10 to 55:45.
[0055] In a preferred embodiment of the rubber composition, a styrene-isoprene-styrene (SIS) copolymer and an ethylene-propylene-diene terpolymer (EPDM) are used in combination. The mass ratio of the styrene-isoprene-styrene (SIS) copolymer to the ethylene-propylene-diene terpolymer (EPDM) is preferably SIS:EPDM=95:5 to 50:50, and more preferably SIS:EPDM=90:10 to 55:45.
[0056] Other optional ingredients In addition to the components (A) and (B), the rubber composition may contain fillers such as calcium carbonate, silica, and carbon black, processing aids, antioxidants, crosslinking agents, and crosslinking accelerators, as long as the effects of the present invention are not impaired. These may be used alone or in combination of two or more. However, from the viewpoint of achieving the effects of the present invention more significantly, it is preferable that the rubber composition does not contain crosslinking agents and crosslinking accelerators.
[0057] The total content of components (A) and (B) in the rubber composition is not particularly limited, but is, for example, 30 to 70 mass%, preferably 40 to 68 mass%, and more preferably 45 to 65 mass%, relative to the total amount of the rubber composition (100 mass%).
[0058] (Calcium Carbonate) From the viewpoint of suppressing migration of the crosslinking agent, it is preferable to use calcium carbonate. As the calcium carbonate, any calcium carbonate conventionally known in the art can be used as appropriate. Although not particularly limited, for example, calcium carbonate that has been subjected to a surface treatment such as hydrophobization may be used. Specifically, for example, calcium carbonate treated with stearic acid, calcium carbonate treated with rosin acid, calcium carbonate treated with lignin, calcium carbonate treated with a fatty acid quaternary ammonium salt, etc. may be used.
[0059] The average particle size (average primary particle size) of calcium carbonate used in the rubber composition is, for example, 10 to 300 nm. From the viewpoint of significantly exhibiting the effects of the present invention, the average particle size (average primary particle size) of calcium carbonate is, for example, preferably 30 to 100 nm, more preferably 30 to 70 nm. The average particle size (average primary particle size) can be calculated using a scanning transmission electron microscope.
[0060] The particle shape of calcium carbonate used in the rubber composition may be, for example, cubic, spindle, disk, hexagonal plate, or spherical. Among these, the cubic shape is preferred from the viewpoint of further improving the damping characteristics. Examples of the cubic shape include a regular hexahedron and a cube that is close to a regular hexahedron. Specifically, for example, a hexahedron with a difference in length between each side of ±8 nm may be mentioned.
[0061] The BET specific surface area of calcium carbonate is, but is not limited to, for example, 4.0 to 60 m 2 / g, preferably 10 to 40m 2 / g, more preferably 20 to 35m 2 / g. The BET specific surface area of calcium carbonate can be measured, for example, by degassing a sample at 200° C. for 15 minutes and then using a mixed gas (N2: 70%, He: 30%) as an adsorption gas with a BET specific surface area measuring device (Microdata Corporation, 4232-II).
[0062] The DBP (dioctyl phthalate) oil absorption of calcium carbonate is, but not limited to, for example, 15 to 75 cc / 100 g, preferably 20 to 45 cc / 100 g, and more preferably 20 to 30 cc / 100 g.
[0063] From the viewpoint of effectively suppressing migration of the crosslinking agent, the content of calcium carbonate is, for example, 25 to 80 parts by mass, preferably 28 to 70 parts by mass, and more preferably 30 to 60 parts by mass, relative to 100 parts by mass of the total of the (A) component and the (B) component.
[0064] (silica) From the viewpoint of suppressing the migration of the crosslinking agent, it is preferable to use silica. As the silica, a conventionally known silica in this technical field can be appropriately used. Although not particularly limited, examples thereof include wet silica, dry silica, and colloidal silica. These can be used alone or in combination of two or more kinds.
[0065] The surface of the silica may be subjected to a hydrophobic treatment, if necessary. As the hydrophobic treated silica, dimethylsilyl-treated silica and trimethylsilyl-treated silica, which are surface-treated with dimethylsilane or trimethylsilane, are preferred.
[0066] The BET specific surface area of the silica is not particularly limited, but is, for example, 350 m 2 / g or less is preferable, and 80 to 320m 2 / g, 100-300m 2 / g. The BET specific surface area of silica can be measured, for example, by degassing a sample at 200°C for 15 minutes and then using a mixed gas (N2: 70%, He: 30%) as the adsorption gas with a BET specific surface area measuring device (Microdata Corporation, 4232-II).
[0067] The DBA adsorption amount of silica is not particularly limited, but is preferably 10 to 350 mmol / kg, and more preferably 20 to 300 mmol / kg. The DBA adsorption amount can be measured from the amount of dibutylamine (DBA) adsorbed to unreacted silanol groups on the silica surface.
[0068] From the viewpoint of effectively suppressing migration of the crosslinking agent, the content of silica is, for example, preferably 20 to 80 parts by mass, and more preferably 30 to 60 parts by mass, relative to 100 parts by mass of the total of the components (A) and (B).
[0069] In one embodiment of the rubber composition, from the viewpoint of significantly achieving the effects of the present invention, it is preferable to contain at least one of calcium carbonate and silica. That is, by containing calcium carbonate and / or silica together with the (A) component and the (B) component, the formation of hardened parts tends to be effectively suppressed, and the deterioration of damping characteristics can be suppressed.
[0070] (Carbon Black) Carbon black may be any of those conventionally known in the art. For example, various grades of carbon black such as SAF, ISAF, HAF, MAF, FEF, GPF, SRF, FT, and MT may be used. These may be used alone or in combination of two or more.
[0071] The nitrogen adsorption specific surface area of carbon black is not particularly limited, but is, for example, 10 to 150 m 2 / g is preferable, and 15 to 100m 2 / g, and even more preferably 20 to 76 m 2 / g, particularly preferably 25 to 65m 2 The nitrogen adsorption specific surface area of carbon black can be measured, for example, by degassing a sample at 200° C. for 15 minutes and then using a mixed gas (N2: 70%, He: 30%) as the adsorption gas with a specific surface area measuring device (Microdata Corporation, 4232-II).
[0072] The iodine adsorption amount of carbon black is not particularly limited, but is, for example, preferably 10 to 150 mg / g, more preferably 10 to 75 mg / g, and even more preferably 20 to 65 mg / g. The DBP (dibutyl phthalate) absorption amount of carbon black is preferably 20 to 180 mL / 100 g, and more preferably 20 to 150 mL / 100 g. The iodine adsorption amount of carbon black is a value measured in accordance with JIS K6217-1 (Method A), and the DBP absorption amount of carbon black is a value measured in accordance with JIS K6217-4.
[0073] The content of carbon black is not particularly limited, but is preferably 0.5 to 15 parts by mass, and more preferably 1 to 10 parts by mass, per 100 parts by mass of the total of the components (A) and (B).
[0074] When silica and carbon black are used in combination, the content ratio of the two (silica:carbon black) is, for example, 98:2 to 70:30, and preferably 97:3 to 80:20.
[0075] (Anti-aging agent) Examples of the antiaging agent include aromatic secondary amine-based antiaging agents, special wax-based antiaging agents, amine-ketone-based antiaging agents, phenol-based antiaging agents, imidazole-based antiaging agents, etc. These may be used alone or in combination of two or more kinds. The content of the antioxidant is not particularly limited, but is, for example, 0.5 to 5 parts by mass, and preferably 1 to 4 parts by mass, per 100 parts by mass of the total of the components (A) and (B).
[0076] (Processing aids) Examples of processing aids include stearic acid, paraffin wax, polyethylene, peptizer, etc. The content of the processing aid is not particularly limited, but is, for example, 0.5 to 5 parts by mass, and preferably 1 to 4.5 parts by mass, per 100 parts by mass of the total of the (A) component and the (B) component.
[0077] [Adhesive layer] In one embodiment of the present invention, the adhesive forming the adhesive layer (hereinafter, sometimes referred to as "the adhesive") contains a polymer component and a crosslinking agent (including a crosslinking accelerator). As the polymer component, those conventionally known in the art can be appropriately used. Examples include, but are not limited to, halogenated polymers, phenolic resins, epoxy resins, graphite polymers, etc. Among these, halogenated polymers are preferred from the viewpoint of adhesion to the metal layer. Examples of halogenated polymers include chlorinated natural rubber, chlorinated polyethylene, chlorosulfonated polyethylene, chlorinated polybutadiene, and brominated polymers.
[0078] From the viewpoint of achieving the effects of the present invention remarkably, the content of the polymer component is 15 to 60 mass % of the total solid content contained in the adhesive, preferably 20 to 55 mass %, more preferably 25 to 50 mass %. Here, the solid content means the solid content excluding the solvent component in the adhesive. As the solvent component, for example, water, xylene, ethylbenzene, methyl isobutyl ketone, etc. are used.
[0079] Examples of the crosslinking agent include aromatic nitroso compounds, aromatic dioximes, aliphatic bis-nitrosamines, maleimide compounds, etc. Specific examples include, but are not limited to, aromatic dinitroso compounds such as m-dinitrosobenzene, p-dinitrosobenzene, m-dinitrosonaphthalene, p-dinitrosonaphthalene, 2,5-dinitroso-p-cymene, 2-methyl-1,4-dinitrosobenzene, 2-methyl-5-chloro-1,4-dinitrosobenzene, 2-fluoro-1,4-dinitrosobenzene, 2-methoxy-1,3-dinitrosobenzene, 5-chloro-1,3-dinitrosobenzene, and 2-benzyl-1,4-dinitrosobenzene. Also, for example, N,N'-(1,3-phenylene)bismaleimide, N,N'-(4-methyl-1,3-phenylene)bismaleimide, N,N'-(1,4-phenylene)bismaleimide, N,N'-(1,2-phenylene)bismaleimide, N,N'-(1,5-naphthylene)bismaleimide, N,N'-(4-chloro-1,3-phenylene)bismaleimide, N,N'-(methylenedi-p-phenylene)bismaleimide, N,N'-(4,4' -biphenylene)bismaleimide, N,N'-(sulfonyldi-p-phenylene)bismaleimide, N,N'-(oxydi-p-phenylene)bismaleimide, N,N'-(3,3'-dimethyl-4,4'-biphenylene)bismaleimide, N,N'-(benzylidene di-p-phenylene)bismaleimide, N,N'-[methylenebis(3-chloro-4-phenylene)]bismaleimide, N,N'-[methylenebis(3-methyl-4-phenylene) ]bismaleimide, N,N'-[methylenebis(3-methoxy-4-phenylene)]bismaleimide, N,N'-(thiodi-p-phenylene)bismaleimide, N,N'-3,3'-benzophenone bismaleimide, N,N'-[methylenebis(3-methyl-5-ethyl-4-phenylene)]bismaleimide, N,N'-[tetramethylenebis(oxy-p-phenylene)]bismaleimide, 2,2-bis[4-(4-maleimidophenoxy)phenyl]bismaleimide, [4-maleimidophenoxy)phenyl]propane, bis[4-(4-maleimidophenoxy)phenyl]sulfone, 1,4-phenylenebis(4-maleimidophenoxy), bis[3-(4-maleimidophenoxy)phenyl]sulfone, bis[4-(3-maleimidophenoxy)phenyl]ketone, 1,3-phenylenebis(4-maleimidophenoxy), and bis[4-(4-maleimidophenylthio)phenyl]ether.
[0080] From the viewpoint of prominently exhibiting the effects of the present invention, the content of the crosslinking agent is preferably 0.1 to 60 mass % relative to the total solid content contained in the adhesive, more preferably 0.1 to 50 mass %, even more preferably 1 to 50 mass %, and particularly preferably 3 to 40 mass %. Furthermore, when a crosslinking agent and a crosslinking accelerator are used in combination, the total content of both is preferably 0.1 to 85 mass %, more preferably 0.1 to 50 mass %, even more preferably 1 to 50 mass %, and particularly preferably 3 to 40 mass %, based on the total solid content contained in the adhesive, from the viewpoint of significantly achieving the effects of the present invention.
[0081] In addition to the above components, the adhesive may optionally contain a filler, a thickener, an acid acceptor, other additives, and subcomponents.
[0082] The adhesive layer may be either a one-component type or a two-component type. When it is a two-component type, the adhesive layer is composed of two layers: an undercoat adhesive layer (also called a primer) formed in contact with the surface of the metal layer, and a topcoat adhesive layer (also called a cover coat) formed in contact with the undercoat adhesive layer, and the topcoat adhesive layer (also called a cover coat) is formed from this adhesive.
[0083] [Metal layer] The metal for forming the metal layer is not particularly limited, but examples thereof include iron, stainless steel, copper, brass, and composite alloys thereof.
[0084] (Method for preparing the present viscoelastic body) The rubber composition can be obtained, for example, by kneading the components (A) and (B), and optionally other components, using a kneader, planetary mixer, mixing roll, twin-screw mixer, or the like.
[0085] Specifically, although not limited thereto, in a production method including a first step of kneading at least the (A) component and the (B) component to prepare a first kneaded product, and a second step of adding calcium carbonate or the like to the first kneaded product and kneading the first kneaded product to obtain a second kneaded product, the first step is kneading under conditions of 80 to 150°C for 3 to 15 minutes (preferably 100 to 120°C for 7 to 12 minutes), and the second step is a method of adding calcium carbonate to the kneaded product obtained in the first step under conditions of adjusting the temperature to a range of 50 to 110°C, kneading for 2 to 10 minutes (preferably 3 to 8 minutes), and then kneading under conditions of 80 to 150°C for 3 to 15 minutes (preferably 100 to 120°C for 7 to 12 minutes).
[0086] (Vibration damper manufacturing method) In a method for manufacturing a vibration damper, for example, a rubber composition (viscoelastic body) is prepared as described above, and multiple metal plates of a predetermined size are prepared. The rubber composition (viscoelastic body) is layered on the metal plate, and finally, the metal plate is layered to produce a laminate. An adhesive is applied to the lamination surface of the metal plate in advance.
[0087] As described above, this vibration damper uses an uncrosslinked viscoelastic material made of a rubber composition containing components (A) and (B) and an adhesive made of an adhesive containing a crosslinking agent, and by controlling the thickness of the hardened portion formed by the crosslinking agent that has migrated from the adhesive layer into the uncrosslinked viscoelastic material layer within a specific range, it is possible to suppress the deterioration of the damping characteristics.
[0088] The manufacturing method for controlling the thickness of the cured portion to a specific range is not particularly limited, but suitable examples include a method of blending calcium carbonate and / or silica in addition to components (A) and (B), a method of adjusting the type of adhesive that forms the adhesive layer, the type of crosslinking agent, and the contents thereof, or a method of heating and pressurizing the laminate under conditions of 120 to 155°C and 30 to 100 minutes (preferably 130 to 145°C and 60 to 90 minutes).
[0089] An example of this vibration damper is shown in Figure 1. In the figure, 1 is the vibration damper, 2 is the viscoelastic body (viscoelastic layer), and 4 and 5 are metal plates (metal layers). The viscoelastic body (viscoelastic layer) is sandwiched between two metal plates 4 and 5 and bonded to the two metal plates 4 and 5 with an adhesive. Fig. 2 is a cross-sectional view (A-A' cross-sectional view in Fig. 1) showing an example of the present vibration damper. Fig. 2 shows a vibration damper in which the viscoelastic body 2 has a single-layer structure. Although not shown, in the present vibration damper, an adhesive (adhesive layer) is applied to and intervenes at the interface between the viscoelastic body 2 (viscoelastic layer) and the metal plate 4 (metal layer), and an adhesive (adhesive layer) is also applied to and intervenes at the interface between the viscoelastic body 2 (viscoelastic layer) and the metal plate 5 (metal layer). Fig. 3 is a cross-sectional view showing another example of a vibration damper. Fig. 3 shows a vibration damper in which the viscoelastic body 2 has a two-layer structure. Although not shown, in this vibration damper, an adhesive (adhesive layer) is applied to and intervenes at the interface between the viscoelastic body 2 (viscoelastic body layer) and the metal plate 4 (metal layer), and an adhesive (adhesive layer) is also applied to and intervenes at the interface between the viscoelastic body 2 (viscoelastic body layer) and the metal plate 5 (metal layer).
[0090] Fig. 4 shows an example of installation of the vibration damper 1. In Fig. 4, 1 is the vibration damper, 2 is a viscoelastic body, 4 and 5 are metal plates, 6 is a bolt, 7 and 8 are panels, 10 is a beam, and 11 is a foundation. As shown in the figure, the metal plates 4 and 5 of the vibration damper 1 are attached to the panels 7 and 8 by the bolt 6, respectively. And, the viscoelastic body 2 sandwiched between the metal plates 4 and 5 functions to damp vibration between the beam 10 and the foundation 11.
[0091] Fig. 7 is a schematic partial cross-sectional view for explaining the layer structure of the vibration damper. With reference to Fig. 7, the thickness (2t) of the viscoelastic layer (2) in the vibration damper is not particularly limited, but is preferably 3 to 40 mm, more preferably 10 to 25 mm, from the viewpoint of significantly achieving the effects of the present invention. The thickness (at) of the adhesive layer (a) in the present vibration damper (the thickness of the top adhesive layer (cover coat) in the case of two layers) is not particularly limited, but from the viewpoint of prominently exhibiting the effects of the present invention, it is preferably 5 to 40 μm, and more preferably 10 to 25 μm. As described above, it is important that the thickness (2h) of the hardened portion in the present vibration damper is controlled to a specific range of 75 μm or less. It is more preferably 10 to 70 μm, even more preferably 20 to 60 μm, even more preferably 20 to 50 μm, particularly preferably 20 to 40 μm, and may be 20 to 30 μm. The thickness (2h) of the cured portion is a part of the thickness of the viscoelastic layer (2), and is the thickness of the portion where the crosslinking agent in the adhesive layer (a) migrates, the crosslinking density increases, and the elastic modulus exceeds 1.2 MPa. Specifically, as shown in Fig. 7, it is the portion of the thickness region in the direction of the viscoelastic layer (2) starting from the interface (s) of the adhesive layer (a) where the elastic modulus exceeds 1.2 MPa. The thickness of the metal layer (4) in the present vibration damper is not particularly limited, but from the viewpoint of prominently exhibiting the effects of the present invention, it is preferably 10 to 40 mm, more preferably 15 to 25 mm. It should be noted that FIG. 7 is a schematic explanatory diagram, and the layer structure, layer thickness ratios, and the like in FIG. 7 are not intended to limit the present invention.
[0092] The vibration damper of the present invention is not limited to the shapes described above, and can exhibit excellent functions as a vibration damper for civil engineering and architectural use (also called a vibration damper), a vibration damper for home appliances and electronic devices, etc. In particular, it can perform better as a vibration damper (also called a seismic damper) used in large structures such as bridges and buildings, and particularly as a vibration damper for high-rise buildings. EXAMPLES
[0093] Next, examples will be described together with comparative examples, but the present invention is not limited to these examples as long as the gist of the present invention is not exceeded.
[0094] First, the following viscoelastic body was prepared. Additionally, the following adhesive was prepared.
[0095] <Viscoelastic body> Viscoelastic body a The components shown in Table 1 below were mixed in the ratios shown in the table to prepare a rubber composition. That is, the rubber composition was prepared through a first step of kneading components (A) and (B) to prepare a master batch, and a second step of adding the remaining materials to the master batch and kneading them. The first step was performed by kneading in a kneader at 130°C for 10 minutes. The second step was performed by adding the remaining materials to the master batch prepared in the first step and kneading them in a kneader at 130°C for 10 minutes.
[0096] Viscoelastic body b Viscoelastic body b was prepared in the same manner as viscoelastic body a, except that silica and calcium carbonate were not contained.
[0097] [Table 1]
[0098] <Adhesive> Adhesive a: Chlorinated natural rubber adhesive (adhesive containing 10% by mass of DNB (dinitrosobenzene) as a crosslinking agent) Adhesive b: Chlorinated natural rubber adhesive [adhesive containing 30% by mass of DNB (dinitrosobenzene) as a crosslinking agent] Adhesive c: Chlorinated natural rubber adhesive [adhesive containing 10% by mass of a bismaleimide compound as a crosslinking agent]
[0099] Example 1 A number of iron plates [20 mm thick, 1200 mm long, 800 mm wide] were prepared, and viscoelastic body a [10 mm thick, 900 mm long, 700 mm wide] and an intermediate iron plate (located between one iron plate and the other iron plate) were alternately stacked on one iron plate, and finally the other iron plate was stacked to create a laminate. Note that adhesive a was applied to the stacking surfaces of the iron plates before the laminate was created.
[0100] The obtained laminate was heat-pressed at 140° C. for 70 minutes to prepare a sample. The thickness of the adhesive layer of each of the obtained samples was 10 μm.
[0101] Example 2 A sample according to Example 2 was obtained in the same manner as in Example 1, except that the adhesive a was changed to adhesive b. The thickness of the adhesive layer of the obtained sample was 20 μm.
[0102] Example 3 Except for changing the adhesive a to adhesive c, a sample according to Example 3 was obtained in the same manner as in Example 1. The thickness of the adhesive layer of the obtained sample was 10 μm.
[0103] Example 4 A sample according to Example 4 was obtained in the same manner as in Example 1, except that the viscoelastic body a was changed to a viscoelastic body b (containing no calcium carbonate and no silica) [thickness 10 mm, length 900 mm, width 700 mm]. The thickness of the adhesive layer of the obtained sample was 10 μm.
[0104] Comparative Example 1 A sample according to Comparative Example 1 was obtained in the same manner as in Example 1, except that the obtained laminate was hot-press molded for 110 minutes at 170° C. The thickness of the adhesive layer of the obtained sample was 10 μm.
[0105] [Measurement of elastic modulus of hardened part] The part of the sample obtained above that contained the laminated structure of the metal layer, adhesive layer, and viscoelastic layer was cut with a metal cutter, embedded in resin, and polished to prepare a smooth cross section, and the elastic modulus of the viscoelastic layer was measured using a microhardness tester to determine the thickness of the hardened part. The results are shown in Table 2. [Elastic modulus measurement conditions] Microhardness tester: Fischer Instruments, FISCHERSCOPE HM2000 Vickers diamond indenter: square pyramid Load: 0~200mN Press time: 2 seconds Maximum load retention (creep) time: 5 seconds Load release time: 2 seconds
[0106] In the present embodiment, the elastic modulus was measured at a location near the interface between the intermediate iron plate and the viscoelastic layer. For convenience, the elastic modulus was measured at intervals of 20 μm from the interface between the adhesive layer and the viscoelastic layer in this example. That is, the elastic modulus was measured at each of the following points to determine the thickness of the cured portion: (1) the position of the interface between the adhesive layer and the viscoelastic layer, (2) a position 20 μm thick from the interface toward the viscoelastic layer, (3) a position 40 μm thick from the interface toward the viscoelastic layer, (4) a position 60 μm thick from the interface toward the viscoelastic layer, (5) a position 80 μm thick from the interface toward the viscoelastic layer, and (6) a position 100 μm thick from the interface toward the viscoelastic layer. Specifically, the above (1) to (6) were measured in order, and the thickness position where the elastic modulus exceeded 1.2 MPa was determined as the thickness of the hardened portion. For example, in Example 1, the elastic modulus exceeded 1.2 MPa at stage (2) and was 1.2 MPa or less at stage (3), so the thickness of the hardened portion was determined to be 20 μm.
[0107] The method for measuring the elastic modulus is not limited to the above measurement intervals, and the elastic modulus can also be measured at smaller measurement intervals (e.g., every 10 μm). In this case, measurements are also performed sequentially, and the thickness position where the elastic modulus exceeds 1.2 MPa is defined as the thickness of the hardened portion. For example, if the elastic modulus at a position 30 μm thick from the interface toward the viscoelastic layer is greater than 1.2 MPa, and the elastic modulus at a position 40 μm thick from the interface toward the viscoelastic layer is 1.2 MPa or less, the thickness of the hardened portion is 30 μm.
[0108] [Attenuation characteristic test] The sample was vibrated in the direction of the arrow in FIG. 5 (the adhesive layer and the cured portion are not shown), and the dynamic shear properties were evaluated based on the load-strain loop curve shown in FIG. 6. That is, a vibration (shear strain rate: 200% (200% of the sample thickness), frequency (f): 0.33 Hz, measurement temperature: 20°C) was applied to the device shown in FIG. 5 using a vibration exciter (DYNAMIC SERVO, manufactured by Washinomiya Seisakusho Co., Ltd.), an input signal oscillator (Synthesized function generator FC320, manufactured by Yokogawa Electric Corporation), and an output signal processor (Portable FFT analyzer CF-3200, manufactured by Ono Sokki Co., Ltd.) assuming a large earthquake, and the equivalent stiffness (Ke) and equivalent damping coefficient (Ce) were calculated according to the following formulas (1) to (3) from the analysis of the shear strain value (δ) and load value (Qd) with respect to the vibration time, and the damping constant (he) was calculated from the values. In the following formula, ω=2πf, W=Keδ 2 / 2, ΔW denotes the load-strain loop area (absorbed energy). Equivalent stiffness: Ke(N / mm)=Qd / δ …(1) Equivalent damping coefficient: Ce(kN·s / m)=ΔW / πωδ 2 …(2) Attenuation constant: he = ΔW / 4πW …(3)
[0109] The damping constant in each of the Examples and Comparative Examples was calculated as an index value when the damping constant in Comparative Example 1 was set to 1.0 (standard), and was evaluated according to the following standard. The results are shown in Table 2. ◎…Attenuation constant (index conversion value) is 1.20 or more ○…Attenuation constant (index conversion value) is 1.05 or more and less than 1.20 ×…Attenuation constant (index conversion value) is less than 1.05
[0110] [Table 2]
[0111] From the results in Table 2 above, it can be seen that the samples of the examples satisfy the requirements of the present invention and therefore have excellent damping characteristics. Specifically, it can be seen that the examples in which the thickness of the hardened portion is controlled to 75 μm or less have excellent damping characteristics.
[0112] In contrast, the results in Table 2 show that the samples of the comparative examples do not satisfy the requirements of the present invention and therefore have insufficient damping characteristics. Specifically, Comparative Example 1, in which the thickness of the hardened portion is 80 μm, which is outside the range of 75 μm or less, had poor damping characteristics.
[0113] Furthermore, a comparison between Example 1 and Example 4 shows that by blending calcium carbonate and / or silica, the thickness of the hardened portion can be further suppressed, resulting in superior damping characteristics.
[0114] The interlayer adhesion properties between the metal layer and the uncrosslinked viscoelastic layer were evaluated for the samples of the examples. The samples of Examples 1 to 4 showed excellent results in terms of the interlayer adhesion properties.
[0115] From the above, it can be seen that a deterioration in damping characteristics can be suppressed if the vibration damper meets the requirements of the present invention, i.e., if the vibration damper has a layered structure formed by laminating, in this order, a metal layer, an adhesive layer made of an adhesive containing a crosslinking agent, and an uncrosslinked viscoelastic layer made of a rubber composition containing components (A) and (B), and has a hardened portion with an elastic modulus of more than 1.2 MPa formed by the crosslinking agent that has migrated from the adhesive layer into the uncrosslinked viscoelastic layer, and the thickness of the hardened portion is in the range of 75 μm or less. [Industrial Applicability]
[0116] The vibration damper of the present invention can exhibit excellent functions as a vibration damper for civil engineering and architectural use, as a vibration damper for home appliances and electronic devices, etc. In particular, it can exhibit more excellent functions as a vibration damper used in large structures such as bridges and buildings, and particularly as a vibration damper for high-rise buildings. In addition, vibration control devices and seismic isolation devices such as vibration control walls for buildings, vibration control materials and shock absorbing materials for home appliances and electronic devices, and vibration control materials and shock absorbing materials for automobiles, which are equipped with the viscoelastic material that is a component of the vibration damper of the present invention, can also be used as the vibration damper of the present invention. [Explanation of symbols]
[0117] 1 Vibration damper 2 Viscoelastic body 4,5 Metal plate 6 Volts 7,8 Panel 10 beams 11 Foundation A. Adhesive
Claims
1. A metal layer; An adhesive layer made of an adhesive containing a crosslinking agent; A vibration damper having a layer structure formed by laminating, in this order, an uncrosslinked viscoelastic layer made of a rubber composition containing the following components (A) and (B): A vibration damper having a hardened portion having an elastic modulus of more than 1.2 MPa formed by the crosslinking agent that has migrated from the adhesive layer into the uncrosslinked viscoelastic layer, the hardened portion having a thickness in the range of 75 μm or less. (A) At least one of a styrene-isoprene-styrene copolymer and a styrene-butadiene-styrene copolymer (B) one or more selected from the group consisting of ethylene-propylene-diene terpolymer, ethylene-butene-diene terpolymer, and butadiene rubber
2. 2. The vibration damper according to claim 1, wherein the hardened portion has a thickness in the range of 50 [mu]m or less.
3. 3. The vibration damper according to claim 1, wherein the rubber composition further contains at least one of calcium carbonate and silica.
4. 3. The vibration damper according to claim 1, wherein the crosslinking agent is an aromatic nitroso compound, and the content of the aromatic nitroso compound is 0.1 to 50 mass % based on the total solid content contained in the adhesive.
5. 3. The vibration damper according to claim 1, wherein the uncrosslinked viscoelastic layer has a thickness of 3 to 40 mm, and the adhesive layer has a thickness of 5 to 40 μm.
Citation Information
Patent Citations
Highly damping elastomer composition for vibration damper and vibration damper obtained by the same
JP2010126597A
High attenuation rubber composition for seismic isolation damper and seismic isolation damper obtained by using the same
JP2014227521A
High attenuation rubber composition for vibration control damper and vibration control damper using the same
JP2015183110A
Earthquake-proof damper
JP2020050774A
Vibration control damper
JP2020139031A